RESPON PERTUMBUHAN Cyperus kyllingia PADA TANAH TERCEMAR LIMBAH MINYAK BUMI DAN ANALISIS POTENSI RANCANGAN HANDOUT PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN KELAS XII SMA - Rika Efrianti; Sri Wulandari; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted to find out the growth response of Cyperus kyllingia on soil contaminated with petroleum waste which used for handout design on growth material and development of XII SMA class which was conducted in November 2016 until February 2017. This research is descriptive quantitative research to know the response of Cyperus kyllingia that planted on soil contaminated with petroleum waste with different concentrations of Total Petroleum Hydrocarbon TPH, while handout design analysis was conducted in two stages, namely the analysis and design phase. Parameters used include degradation rate (%) TPH and vegetative growth of crops, ie shoot number, stem height, leaf length, wet weight and dry weight of plant. The data obtained were analyzed descriptively quantitatively. The results showed that the Cyperus kyllingia plant was able to grow on contaminated soil of petroleum waste. The response of plants in the face of stress can be seen in vegetative growth in the form of growth of shoot number, stem height and leaf length. The higher the concentration of TPH on the soil the lower the growth rate. Cyperus kyllingia plant has the ability to degrade TPH with a percentage of 0.32-0.39%. The results can be developed into handouts on the growth and development for grade XII SMA.Key Word: Vegetative Growth, Cyperus kyllingia, Polluted Land, Handout.